Gray Divorce at Palembang Religious Court 2022: Factors Associated with Old Age Divorce - Putri, Ellis Lindini; Dewi, Rusmala; Azhari, Ari (UIN Sunan Kalijaga Yogyakarta, 2023)
Divorce is a phenomenon that is experienced in various age ranges, including among the elderly showing an increasing trend. Previous studies emphasize the negative impact of divorce in old age. This study aims to identify the factors that lead to divorce among the elderly, particularly in the Palembang Religious Court, as well as understand the judges' views on this phenomenon. This field research used a qualitative approach, involving interviews with four judges and analyzing 56 divorce decisions among the elderly. The findings show that elderly couples tend to delay divorce in order to sustain the household, especially for the sake of their children. The decision to divorce is made when they feel unable to endure further problems, considering the greater impact. Thirteen main factors were cited as reasons why elderly couples decided to divorce. While judges attempted mediation, they did not have the authority to force a settlement. The results of this study are expected to provide valuable guidance for legal practitioners and policy makers in designing programs to prevent divorce at an elderly age. The limitation of this study lies in its focus only on the views of judges and decisions in religious courts. Examining the opinions of older people who have divorced directly has not been done, an aspect that needs further research.[Perceraian merupakan fenomena yang terjadi di berbagai rentang usia, termasuk di kalangan lansia yang menunjukkan peningkatan tren. Kajian sebelumnya menegaskan dampak negatif dari perceraian di usia lanjut. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang memicu perceraian di kalangan lansia, khususnya di Pengadilan Agama Palembang, serta memahami pandangan hakim terhadap fenomena ini. Penelitian lapangan ini menggunakan pendekatan kualitatif, melibatkan wawancara dengan empat hakim dan menganalisis 56 putusan perceraian di kalangan lansia. Temuan menunjukkan bahwa pasangan lanjut usia cenderung menunda perceraian demi mempertahankan rumah tangga, terutama demi anak-anak mereka. Keputusan bercerai diambil ketika mereka merasa tak mampu lagi menahan permasalahan lebih lanjut, dengan pertimbangan dampak yang lebih besar. Terdapat tiga belas faktor utama yang menjadi alasan pasangan lanjut usia dalam memutuskan perceraian. Meskipun hakim berupaya melakukan mediasi, namun mereka tidak memiliki kewenangan untuk memaksa perdamaian. Hasil penelitian ini diharapkan memberikan panduan berharga bagi praktisi hukum dan pembuat kebijakan dalam merancang program pencegahan perceraian di usia lanjut. Keterbatasan penelitian ini terletak pada fokusnya yang hanya pada pandangan hakim dan putusan di pengadilan agama. Menguji pendapat lansia yang telah bercerai secara langsung belum dilakukan, menjadi aspek yang perlu diteliti lebih lanjut.]